WHAT EVERY PSYCHOLOGIST AND PSYCHOTHERAPIST SHOULD KNOW ABOUT THE PLACEBO AND NOCEBO EFFECT - Giacomuzzi, Salvatore; Ertl, Markus; Barinova, Natalia; Garber, Klaus; Kocharian, Alexander (My University, 2021)
Purpose. Only a few medical terms are used as often, even in a metaphorically way, as the words placebo and nocebo. Almost any psychologist and psychotherapist think he/she knows well what by a placebo or nocebo is understood, but usually without really being able to explain it exactly and how it works. In addition, most psychologists and psychotherapists immediately think of clinical trials. However, many things are attributed to the placebo or nocebo effect that does not really fall under this concept in terms of a strict scientific terminology. Therefore, the following article summarizes the ongoing debate on placebo/nocebo effects by citing the current scientific literature. Methods. To realize the purpose of the study, we used the methods of theoretical scientific research. Results. In summary patients are more prone to develop nocebo effects are those with alternative or negative healthcare beliefs or experiences or unrealistic perceptions about treatment; managing these factors is a core strategy to counteract the nocebo effect. Conclusions. Healthcare professionals can help to minimise the influence of the nocebo effect by considering how information about treatments, including benefits and adverse effects, is framed and communicated. Establishing a positive interaction from the start and involving patients in decisions about their treatment and ensuring they understand the cause of their illness and what they can do to manage their symptoms is likely to lead to better treatment outcomes.

Мета. Лише декілька медичних термінів використовуються так часто, навіть у метафоричному плані, як слова плацебо та ноцебо. Майже будь-який психолог і психотерапевт вважає, що він / вона добре знає, що розуміють під поняттями плацебо або ноцебо, але, зазвичай, не можуть пояснити, як саме це працює. Крім того, більшість психологів та психотерапевтів одразу замислюються про клінічні випробування. Однак багато речей приписують ефекту плацебо або ноцебо, який насправді не підпадає під цю концепцію з точки зору суворої наукової термінології. Тому наступна стаття підсумовує поточні дискусії щодо ефектів плацебо / ноцебо, посилаючись на сучасну наукову літературу. Методи. Для реалізації мети дослідження ми використовували методи теоретичного наукового дослідження. Результати. Таким чином, пацієнти більш схильні до розвитку ефектів ноцебо - це ті, хто має альтернативні або негативні переконання в галузі охорони здоров'я або досвід або нереальне сприйняття лікування; управління цими факторами є основною стратегією протидії ефекту ноцебо. Висновки. Медичні працівники можуть допомогти мінімізувати вплив ефекту ноцебо, використовуючи спосіб формування та передачі інформації про лікування, включаючи переваги та несприятливі ефекти. Встановлення позитивної взаємодії з самого початку та залучення пацієнтів до рішень щодо їх лікування та забезпечення розуміння ними причини їхньої хвороби та того, що вони можуть зробити для лікування своїх симптомів, швидше за все, призведе до кращих результатів лікування.
Що кожен психолог і психотерапевт повинен знати про ефект placebo і nocebo
Keywords: placebo; nocebo; healthcare; patients; psychotherapist; 159.99:615.851